LEGAL REGULATIONS OF UAVS IN POLAND AND FRANCE - Karolina HELNARSKA; Jacek KRAWCZYK; Grzegorz MOTRYCZ (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents issues related to legal regulations pertaining to unmanned aerial vehicles (UAVs) in Poland and France. It describes commercial and non-commercial rules of UAV use. It also summarizes conditions concerning UAV weight, procedures of personnel and certification, as well as the space where UAVs may perform flight operations. Additionally, the application and use of UAVs in civil and military environments are described. It allows for the statement that the UAV role in air transport is increasing. Due to the benefits they offer, such as the possibility to remain in the air for a long time, performing flight operations in a harmful environment and little influence on the natural environment, UAVs will be increasingly important and systematically replacing manned aircraft.